The Influence of Field Work Practical Experience and Motivation to Enter the Industrial World on the Work Readiness of Class XII Students at Vocational School State 1 Ratahan Southeast Minahasa Regency - Kuhu, Maikel Wolter; Rompas, Parabelem Tinno Dolf; Olii, Djami (International Journal of Information Technology and Education, 2023)
This research aims to determine the influence of practical fieldwork experience and motivation to enter the world of work on the work readiness of class XII students at SMK Negeri 1 Ratahan Kab. Southeast Minahasa. The population in this study was all class The type of research contained in this research uses quantitative research. data collection techniques using questionnaires. Data processing uses inferential analysis techniques, Multiple Linear Regression Analysis; Regression Line analysis of variance; classical assumption test, Multicollinearity Test, Heteroscedasticity Test, Normality; F test, and t test with the help of the IBM SPSS program for Windows 25.0. The results of the research show that the general description of the experience of fieldwork practice and motivation for entering the world of work on the work readiness of class XII students at SMK Negeri 1 Ratahan is included in the high category. Fieldwork practice experience and motivation to enter the world of work influence students' work readiness by 57.3%. This research concludes that there is a positive and significant influence between practical fieldwork experience and motivation to enter the world of work on students' work readiness, both partially and simultaneously.